Expanding the Chondroitin Sulfate Glycoproteome — But How Far? - Noborn, Fredrik; Nikpour, Mahnaz; Persson, Andrea; Nilsson, Jonas; Larson, Göran (Frontiers in Cell and Developmental Biology, 2021)
Chondroitin sulfate proteoglycans are found at cell surfaces and in connective tissues, where they interact with a multitude of proteins involved in various pathophysiological processes. From a methodological perspective, the identification of chondroitin sulfate proteoglycans is often difficult, as the identification requires the combined sequencing of specific core proteins, together with the characterization of any CS polysaccharide modification(s). According to the current notion of chondroitin sulfate proteoglycans, they are often considered in relation to a functional role in which a given proteoglycan regulate a specific function in cellular physiology. Recent advances in glycoproteomic methods have, however, enabled the identification of numerous novel chondroitin sulfate core proteins in humans and in various animal models. In addition, these methods have revealed unexpected structural complexity even of the linkage regions. These findings indicate that the number and structural complexity of chondroitin sulfate proteoglycans are much greater than previously appreciated. In the light of these findings, the possibility of finding additional chondroitin sulfate proteoglycans, using improved methods and studying novel sample matrices in humans and in animal models is discussed. Further, as many of the novel chondroitin sulfate proteoglycans are found in low abundance and with no yet assigned functions, these findings may challenge the traditional notion of defining proteoglycans. Therefore, the concept of proteoglycans is considered, discussing whether ‘a proteoglycan’ should be viewed mainly on the basis of an assigned function vis-à-vis structural evidence of its existence.